2005
DOI: 10.2169/internalmedicine.44.200
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Macrolide Antibiotic Therapy in the Treatment of Chronic Small Airway Disease Clinically Mimicking Diffuse Panbronchiolitis

Abstract: Objective In the current studies, we investigated the clinical effects of long-term macrolide antibiotic therapy for patients with chronic small airway disease (CAD) that clinically and radiologically mimics but is pathologically distinct from diffuse panbronchiolitis (DPB).Patients and Methods Twenty-one Japanese patients were selected on the basis of clinical criteria for DPB and were categorized as DPB or CAD following histological evaluation of surgical lung biopsies. All patients received long-term macrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The same authors later reported on longterm macrolide antibiotic therapy in the treatment of chronic small-airway disease that clinically mimicked DPB but had a very different histology. Unlike the 80 to 90% response to long-term erythromycin therapy reported for DPB, pulmonary function, total cell counts, and neutrophil percentages in bronchoalveolar lavage fluid did not improve in these patients (121). However, similar to the case for patients with DPB, there were no reported side effects seen with long-term use.…”
Section: Long-term Macrolide Safetymentioning
confidence: 41%
“…The same authors later reported on longterm macrolide antibiotic therapy in the treatment of chronic small-airway disease that clinically mimicked DPB but had a very different histology. Unlike the 80 to 90% response to long-term erythromycin therapy reported for DPB, pulmonary function, total cell counts, and neutrophil percentages in bronchoalveolar lavage fluid did not improve in these patients (121). However, similar to the case for patients with DPB, there were no reported side effects seen with long-term use.…”
Section: Long-term Macrolide Safetymentioning
confidence: 41%
“…This kind of heterogeneity in the response to macrolides is similar to that observed in participants with diffuse panbronchiolitis and small airways disease, where clinical improvements were observed in both groups but only those with diffuse panbronchiolitis had reductions in neutrophils [31]. The study of Albert and colleagues elegantly show the improvement in exacerbation rate and health status in COPD, however they did not assess changes in airway inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…However, they have a different genetic background, so these cases may be forme fruste cases of DPB or cases without the full-blown morphological and clinical expression, and may be more frequent in this population than previously thought. The beneficial effects of macrolides have been documented in some of these cases [93].…”
Section: Resultsmentioning
confidence: 99%